Characterization of alcohol consumption patterns among older adults in Ireland. (13th November 2019) - Guzman, V; McEvoy, C T; McHugh-Power, J; Kenny, R A; Feeney, J
Abstract: Background: Identifying the factors associated with hazardous drinking patterns and problem drinking is imperative to develop appropriate intervention strategies for alcohol harm reduction among the older population. The aim of this study was 1) To explore the patterns of alcohol consumption among older adults in the Republic of Ireland, and 2) To establish possible predictors of hazardous and problem drinking in this population. Methods: A cross-sectional analysis was carried out on samples of individuals aged >50 years at Wave 3 of The Irish Longitudinal Study on Ageing (N = 4948). Hazardous alcohol consumption was defined as drinking above Irish guidelines [women >11 Standard Irish Drinks (SD)/week; men >17 SD/week], and/or having at least one heavy drinking episode per week (>6 SD/day). Problem drinking was defined as a score of > 2 on the CAGE instrument. Regression analyses investigated outcome differences according to socio-demographic and health characteristics. Sampling weights were applied to account for differential non-response. Results: The prevalence of drinking patterns was 13% for lifetime alcohol abstainers, 8% for former drinkers, 26% for occasional drinkers and 53% for weekly drinkers. Among weekly drinkers 25% exceeded the guideline threshold, 23% had at least one heavy drinking episode per week and 16% had an alcohol problem according to the CAGE. In fully adjusted models, hazardous drinking and problem drinking were associated with younger older adults, male sex, current or past smoking, higher levels of stress and/or social isolation. Conclusions: Our findings serve as a starting point to monitor trends of alcohol consumption among older adults in the Republic of Ireland. Our results highlight areas of opportunity for targeted screening and public interventions that seek to reduce alcohol harm among this population. Key messages: In the Irish context, older adults who are younger, male, current or past smokers, with higher levels of stress and/or social isolation are more likely to engage in hazardous alcohol consumption. Our characterization of drinking patterns highlights areas of opportunity for targeted screening and public interventions that seek to reduce alcohol harm among older adults in Ireland.